Selling music for a song [online music]. - Cherry, S. (IEEE spectrum)
Contrary to popular belief, online music services including Apple Computer Inc.'s iTunes Music Store do not turn in huge profits. In the case of Apple, out of the 99 cents that is being charged for a song, about 65 cents goes to the music label that recorded it. Another 25 cents goes for distribution costs and the rest goes to marketing, promotion, and other expenses. To make more money, many musical artists have begun selling their music on their own Web sites. Instead of going to major record labels, others are turning to one another. A prime example is MUDDA (Magnificent Union of Digitally Downloading Artists), which acts as an online collective for artists to sell their music directly to the public. There are other ways digital music will make money for its artists. One of the most sophisticated is an artist-authorized equivalent of the concert tapes that fans have always made. A new service, eMusicLive, will make a recording at a live concert and then sell it on a CD or USB key drive to departing patrons, minutes after the last encore. For more and more musicians, the fruits of new technologies may get the rent paid better than traditional recording contracts.